Renal replacement therapy in critically ill liver cirrhotic patients—outcome and clinical implications. (5th April 2017) - Staufer, Katharina; Roedl, Kevin; Kivaranovic, Danijel; Drolz, Andreas; Horvatits, Thomas; Rasoul‐Rockenschaub, Susanne; Zauner, Christian; Trauner, Michael; Fuhrmann, Valentin
Abstract: Background & Aims: Current guidelines discourage renal replacement therapy (RRT) in critically ill cirrhotics in the lack of liver transplant (LT) options. This study aimed to identify patients who benefit from RRT in the short and long‐term. Methods: Critically ill cirrhotics were included over a time period of 6 years and followed for at least 1 year. CLIF‐C ACLF, CLIF‐SOFA, SOFA and MELD scores on admission, 24 h prior to RRT, 24 and 48 hours after start of RRT were analysed for their predictive value of ICU‐mortality. Additionally, long‐term renal recovery and successful bridging to LT was assessed. Results: In total, 40% (78/193) of patients required RRT. ICU‐, 28 days‐, 90 days‐, and 1 year‐mortality was 71%, 83%, 91%, and 92%, respectively, and was significantly higher than in patients without need for RRT (4%, 30%, 43%, and 50%), P <.001. CLIF‐C ACLF and CLIF – SOFA scores within 24 hours prior to RRT showed good discriminant power to predict ICU‐mortality. CLIF‐C ACLF calculated 48 hours after commencing RRT was the most suitable predictor of ICU‐mortality in RRT‐patients irrespective of LT options (AUC: 0.866). In patients with ≥5 organ failure assessed by CLIF‐SOFA at any time point showed 100% ICU‐mortality. 13% of patients with RRT showed renal recovery; 14% of patients could be bridged to LT. Conclusions: Mortality in critically ill cirrhotics with need for RRT is substantially high independent of LT options. Only a small proportion showed renal recovery after ICU discharge. CLIF‐C ACLF and CLIF‐SOFA score may assist in identifying patients who would not benefit from RRT. Abstract : See Editorial on Page817